River network travel time is correlated with dissolved organic matter composition in rivers of the contiguous United States. Issue 5 (17th May 2021) - Hosen, Jacob D.; Allen, George H.; Amatulli, Giuseppe; Breitmeyer, Sara; Cohen, Matthew J.; Crump, Byron C.; Lu, YueHan; Payet, Jérôme P.; Poulin, Brett A.; Stubbins, Aron; Yoon, Byungman; Raymond, Peter A.
Abstract: Most terrestrial allochthonous organic matter enters river networks through headwater streams during high flow events. In headwaters, allochthonous inputs are substantial and variable, but become less important in streams and rivers with larger watersheds. As allochthonous dissolved organic matter (DOM) moves downstream, the proportion of less aromatic organic matter with autochthonous characteristics increases. How environmental factors converge to control this transformation of DOM at a continental scale is less certain. We hypothesized that the amount of time water has spent travelling through surface waters of inland systems (streams, rivers, lakes, and reservoirs) is correlated to DOM composition. To test this hypothesis, we used established river network scaling relationships to predict relative river network flow‐weighted travel time (FWTT) of water for 60 stream and river sites across the contiguous United States (3090 discrete samples over 10 water years). We estimated lentic contribution to travel times with upstream in‐network lake and reservoir volume. DOM composition was quantified using ultraviolet and visible absorption and fluorescence spectroscopy. A combination of FWTT and lake and reservoir volume was the best overall predictor of DOM composition among models that also incorporated discharge, specific discharge, watershed area, and upstream channel length. DOM spectral slope ratio (R 2  = 0.77) and Freshness Index (R 2  = 0.78) increased and specific ultraviolet absorbance at 254 nm (R 2  = 0.68) and Humification Index (R 2  = 0.44) decreased across sites as a function of FWTT and upstream lake volume. This indicates autochthonous‐like DOM becomes continually more dominant in waters with greater FWTT. We assert that river FWTT can be used as a metric of the continuum of DOM composition from headwaters to rivers. The nature of the changes to DOM composition detected suggest this continuum is driven by a combination of photo‐oxidation, biological processes, hydrologically varying terrestrial subsidies, and aged groundwater inputs. Abstract : Flow‐weighted travel time (FWTT) of water through a river network can be estimated using hydraulic scaling laws. Across the contiguous United States, organic matter composition is correlated to river network FWTT of water when sampled. As FWTT in freshwater systems increases, organic matter consistently transitions from terrestrial to aquatic in character.